Penerapan Algoritma Elephant Herding Optimization (EHO) pada Masalah Hybrid Flowshop Scheduling (HFS) - Ahmad Kamsyakawuni; Khurnia Palupi; Agustina Pradjaningsih (Journal of Applied Informatics and Computing, 2020)
The industry is the driving force for the economy in Indonesia. One of the problems faced by industrial companies in the production process is determining the production schedule. The production schedule that is not according to the specified target can cause losses to the company. Scheduling is the allocation of resources to carry out a set of work at a specified time. The problem solved in this article is hybrid flowshop scheduling (HFS), it’s will be applied to companies engaged in bread making. A solution to solve the HFS problem using elephant herding optimization (EHO) algorithm. For the company to complete the production process by minimizing makespan, effective scheduling is needed, taking into account the number of parallel machines. The results of this article are 9 jobs and makespan 11.270 seconds using the MATLAB software.